Dietary supplementation of black cumin seed meal on rumen fermentation in goats - Kathiraser, Thayalini (2015)
Improving production is important in ruminant industry and to solve this problem, much effort has been carried out to manipulate the rumen ecosystem as it plays an important role in ruminant nutrition. The use of herbal by-products has been considered in order to maximize the usage of herbs and to reduce feed cost. Black cumin seed meal is the by-product of Nigella sativa seed that has been pressed to produce oil and is also believed to contain nutrients that are not fully removed from the whole seed. As such, the present study was to evaluate the effect of black cumin seed meal supplementation on nutrient digestibility, rumen fermentation characteristics, rumen fatty acid profiles and rumen total protozoal counts of goats fed with black cumin seed meal-based feed. In the first part of the study, proximate analysis, fatty acid profiling and determination of saponin and flavonoid of the black cumin seed meal were conducted. In this study, total of five rumen fistulated mixed breed male goats between 18 kg to 20 kg of body weight were used. All goats were fed on 1.5% dry matter (DM) of body weight with formulated concentrate diets supplemented with four levels of black cumin seed meal and 1.5% DM of body weight guinea grass hay as basal diet. The four levels of black cumin seed meal were fixed at 0% (BC0), 0.8% (BC8), 1.6% (BC16) and 2.4% (BC24). The goats were subjected to a three week cycle consisting of two weeks adaptation and one week of experimentation. After one week of washout period, the cycle was resumed. The feeding regime consisted diets supplemented with different levels of black cumin seed meal with guinea grass hay, ad libitum feeding. Results had shown that the black cumin seed meal had 31.2% crude protein,19.2% crude fat, 56% linoleic acid and 0.41% linolenic acid. The saponin content in the black cumin seed meal was about 0.139 mg /100 g while flavonoid content about 3.0 mg / 100 g. The pH of rumen in goats fed with dietary treatments ranged from 6.5 to 7.0 throughout the study. The supplementation of black cumin seed meal had no effect (P>0.05) on all the fatty acid proportions. There were also no significant differences (P>0.05) between dietary treatments on the total VFA concentrations, molar proportions of individual VFA, or ratio of acetate to propionate. The total mean protozoa numbers were also constant throughout the study. In conclusion, the supplementation of black cumin seed meal at 0.8%, 1.6% and 2.4% in the diets did not affect nutrient digestibility, rumen fermentation characteristics, rumen fatty acid profiles and total protozoa counts of the goats.